교회의 분쟁과 교회재산의 귀속에 관한 판례의 동향 - 김상찬(Sang-Chan, Kim); 김상명(Sang-Myeong, Kim) (법학연구, 2013)
본 연구는 일부교인의 집단적 탈퇴로 인한 교회의 분열, 소속교단의 변경결의로 인한 교회재산의 귀속 등에 대한 대법원 판례의 동향을 전반적으로 살피면서, 교회분열과 교회재산 귀속관계의 기준을 검토하고 있다. 교회분열과 교회재산 귀속에 관한 대법원 판례는 1950년대부터 지금까지 변천을 거듭하여 왔는데, 일반적으로 교회는 ‘법인 아닌 사단’이고, 그 기본적 재산관계는 ‘총유’라고 하고 있다. 처음에는 교회의 분열을 인정하고 있었으나, 2006년 대법원 판결에서는, 교인의 집단탈퇴로 교회의 분열로 이어진 경우에도 교회의 분열을 인정하지 않으며, 교단이 변경된 경우에도 종전 교회의 재산은 그 교회에 소속된 잔존 교인들의 총유에 속하고, 종전 교회에서 이탈한 교인들은 더 이상 종전 교회의 재산에 대한 권리를 보유할 수 없다고 판시하고 있다. 이 논문은, 이러한 대법원 판례가 교회의 분열을 영구적으로 방치하고 있다는 학설의 비판을 받아들인 것으로서 타당하며, 교회분쟁을 종결시키는데 도움을 줄 것으로 생각하지만, 교단변경은 종전교단에 소속하였던 교회의 교인들이 그 교회를 해체하고 새로운 교단에 소속된 교회를 새롭게 조직하는데 이르는 것으로 평가하여야 하므로 의결정족수를 2/3 이상의 동의를 요구할 것이 아니라 사단법인의 해산결의에 관한 민법 제78조를 유추적용하여 3/4 이상의 동의를 요구하는 것이 바람직하다고 주장한다. 지금까지의 교회분쟁에 다른 교회재산 귀속에 관한 대법원 판례는 주로 장로교회 등 사단적 구조를 취하고 있는 교단 내에서의 분쟁을 다룬 것이 대부분이어서, 일률적으로 교회는 ‘법인 아닌 사단’이고, 교회의 재산은 ‘총유’에 속한다는 것을 기본적 전제로 하고 있는데, 이와 같이 획일적으로 논할 것이 아니라, 교회가 채택하는 정체, 그리고 교회가 사단적 구조를 취하는지 재단적 구조를 취하는지, 그리고 교회재산의 형성과정과 그 출연자의 출연의사, 그리고 그와 같이 형성된 교회재산이 지니는 기능 등에 대하여 충분히 검토한 후 교회를 ‘법인 아닌 사단’으로 볼 것인지, 그리고 교회재산을 ‘총유’로 할 것인지를 정해야 한다고 주장하고 있다. This study conducts a general review of trends of the Supreme Court's precedents on belonging of church property arising from church divisions due to group withdrawal of some church members and alteration resolution of religious bodies, and also examines the criteria of church divisions and belonging of church property. The Supreme Court's precedents on church divisions and belonging of church property have continued to change from the 1950s until now, and generally have ruled that a church is an 'aggregate corporation instead of a corporate body' and basic state of property is 'overall ownership’. Initially, they admitted church divisions, while in the Supreme Court‘s ruling in 2006, church divisions were not accepted even arising from group withdrawal of church members and property of a previous church belonged to overall ownership of remaining members despite change of the religious body, and members who had withdrawn from previous church were not entitled to the property rights of a previous church. This treatise considers this ruling of the Supreme Court, which accepted the theory in support of prevention of permanent church divisions, might be reasonable and help curb disputes in churches. That said, alteration of religious bodies as such should be deemed as a new establishment of a church belonging to a different body, following the dissolution of the previous one by church members. Therefore, the study suggests that quorum for resolution should ideally be altered to consent more than three-fourths from two-thirds by analogical inference of the Civil Law Article 78. And most of the Supreme Court‘s precedents on belonging of church property arising from church divisions up to now have dealt with disputes within churches in the form of an aggregate corporation such as Presbyterian Church, which presumes that all churches are an 'aggregate corporation instead of a corporate body’ and church property is overall ownership. And from this uniform approach, this study suggests that the judgement of whether a church is an aggregate corporation instead of a corporate body and whether church property is overall ownership, should be made after enough examination of identity pursued by churches, whether a church has structure of an aggregate or corporate body, formation process of church property and intentions of the contributors, functions of church property formed as such. KCI Citation Count: 2